Efficacy and safety of oral dapsone in acne vulgaris – experience of a tertiary care teaching hospital in central Lahore - Chaudhry, Sadaf Amin; Zafar, Nadia Ali; Hayat, Rabia; Noreen, Ayesha; Ali, Gulnaz; Raza, Zain Ali; Nadeem, Muhammad (Journal of Fatima Jinnah Medical University, 2020)
Background: Acne is the eighth most prevalent disease affecting 9.4% of the population worldwide and its prevalence in our country is estimated to be around 5%. Severe inflammatory acne is most likely to leave scars and in order to prevent facial disfigurement due to acne scarring, early treatment is desirable. Various treatment options have been formulated for acne, and are tailored according to the severity of the disease. Numerous clinical trials have been conducted till now, to determine the usefulness and side effect profile of such therapies, making acne treatment a highly studied area in dermatology. Objective of this study is to highlight the fact that oral Dapsone could be used as a cheaper alternate to isotretinoin in recalcitrant severe acne, especially in females where retinoids are sometimes contraindicated. Patients and methods: 51 patients, suffering from severe nodulocystic acne, fulfilling the criteria, were enrolled from the Department of Dermatology, Sir Ganga Ram Hospital, Lahore. All the study patients were given oral Dapsone 50mg for initial two weeks and then 100mg daily for the next 10 weeks along with oral cimetidine and topical clindamycin application twice daily. Investigator Global Assessment Scale (IGAS) was employed to measure effectiveness. The treatment was considered ʽeffectiveʹ if the patient achieves 2 or more than 2-grade improvement or almost clear or clear skin at the end of 12 weeks according to IGAS scale. The lesion counts were also done before the start of therapy (day 1) and at every two weeks follow up for 12 weeks. The change in lesion count observed between the baseline number and that seen at follow up visits was also used to evaluate the effectiveness of oral Dapsone. Safety was analyzed by fortnightly visits of the patients to look for any undesirable side effects and monitoring of the hematologic profile of the patients. Final follow up was done at the end of 16 weeks. Results: The study was conducted on 51 patients, with a ratio of 1:3 for males and females and a mean age of 25.2 years (SD ±5.81). At 12th week, patients had significant reduction in their acne lesions; with 7 patients (13.7%) showing completely clear skin, 17 patients (33.3%) had almost clear skin, 5 patients (9.8%) had 3-grade improvement. Twelve patients (23.5%) had 2-grade improvement from baseline score and only 2 patients (3.9%) had 1-grade improvement from baseline. Based on percentage reduction of lesions, excellent response was seen in 32 patients (62.7%), good response in 9 patients (17.6%), moderate response in 2 patients (3.9%), while no patient showed poor response. Dapsone was discontinued in 8 patients due to derangement of hematologic profile. Conclusion: Oral Dapsone, when given carefully, is a very effective therapeutic option in severe recalcitrant acne, with limited side effects.